Antibiotic Resistance Pattern and Frequency of mecA Gene in Staphylococcus aureus Isolated from Shohada Hospital, Tabriz - Farzaneh Khoei; Haedeh Mobaiyen; Mohamamad Reza Nahaei; Sanam Sadeghi Mohammadi (Pasteur Institute of Iran, 2014)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) can cause serious and life-threatening hospital- and community-acquired infections. Colonized and infected patients represent the most important reservoir of MRSA in health care facilities. Therefore, in this study, MRSA isolates collected from Shohada Hospital in Tabriz were evaluated for the frequency of mecA gene and their antimicrobial susceptibility in a period of three years, from 2010 to 2012. Methods: A total of 182 S. aureus isolates were collected from clinical specimens and first genotypically identified by detection of nuc gene. Antimicrobial susceptibility test was performed by disc agar diffusion method using cefazolin, methicillin, tetracycline, and cefoxitin according to clinical and laboratory standards institute (CLSI) recommendation. Phenotypic (cefoxitin 30 µg/disc) and genotypic (mecA gene detection by PCR) methods were used for detecting methicillin sensitivity. Results: All isolates expressed S. aureus specific sequence gene (nuc) in their PCR products. Eighty-one (44.5%) isolates were confirmed as MRSA by cefoxitin disc screening test and 97 (53.3%) isolates by showing the presence of mecA gene. All the methicillin sensitive S. aureus (MSSA) isolates and 64 (66%) MRSA isolates were found to be susceptible to cefazolin, but 25 (25.8%) MRSA were resistant to tetracycline and cefazolin. Conclusion: The results of this study showed high frequency (53.3%) of MRSA with no significant differences in rates within the three years of study, indicating the inefficiency of control programs to care for patients with MRSA.